MANAJEMEN PESERTA DIDIK DENGAN PENDEKATAN PROJECT BASED LEARNING BERBASIS KOLABORATIF DALAM MENINGKATKAN PRESTASI SISWA DI SD NEGERI - Marsithah, Iis (Universitas Islam Negeri Sumatera Utara Medan, 2024)
An independent curriculum is a curriculum that gives teachers the freedom to choose various learning models that will be applied in class and can be adapted to the learning needs and interests of students. One of them is the Project Based Learning learning model. Project Based Learning is a learning activity in the form of creating products or services that are used as a means of mastering competencies. This research aims to improve student learning outcomes through a collaborative-based Project Based Learning learning model. The variables in this research consist of the independent variable, namely the Project Based Learning (PjBL) learning model and the dependent variable, namely student learning outcomes. The data collection technique in this research uses triangulation techniques. Based on the results of this research, it can be concluded that learning using the Project Based Learning model can improve student learning outcomes